การปรับปรุงวิธีไฟไนต์อีลีเมนต์เพื่อวิเคราะห์ไอเกนโมดในท่อนำคลื่นมีสันโดยใช้อีลีเมนต์ขอบแบบเอกฐานและการปรับแบบจำลองไฟไนต์อีลีเมนต์ - สุวิชาญ กาวาฮารา (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
This thesis presents the improvement of finite element method analysis ridge waveguides in 2 dimensional. The structure of ridge waveguides make to be fast variation electromagnetic wave at region corner. So, the analysis ridge waveguides is slower convergence rate than general waveguides when use FEM. This thesis proposes the 2 methods of improvement convergence rate of FEM. The first method uses singular edge element shape function to model at the region corner combine with normal edge element shape function. The second method uses adaptive meshing. Both methods must satisfy the variation of electromagnetic wave in ridge waveguides. This thesis computes by using 4 shape functions are as follow : normal constant edge element, singular constant edge element, normal linear edge element and singular linear edge element. Simulation results, it is found that the presented shape functions are good convergence rtae respectively. And the convergence rate of the adaptive meshing better than the general discretization. The simulation results in this thesis are inclined to the reference paper.